RENCANA PENATAAN KAWASAN WISATA TELAGA BIRU CISOKA, KABUPATEN TANGERANG - Sahda Salsabila; Suryono Herlambang; Parino Rahardjo (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2021)
The Telaga Biru Cisoka Tourism Area is a post-sand excavation area that is a tourist destination, which has 3 (three) lakes with different colors and 1 (one) lake as a Retention Basion. The Telaga Biru Cisoka Tourism Area has tourism potential based on agro-tourism and sports. The existence of tourist attractions such as Telaga Biru Cisoka can make an attraction to meet the needs of local residents and increase regional economic income. The purpose and objective of this research is to propose a structuring plan for the Telaga Biru Cisoka Tourism Area and get the results in the form of a Telaga Biru Cisoka Tourism Area master plan. This is in order to optimize the potential of the Telaga Biru Cisoka Tourism Area and to realize it as an agro-tourism and sports area then become input or recommendations to stakeholders who play a role in planning. Based on the results of the analysis, the Telaga Biru Cisoka Tourism Area has 3 (three) zoning in its arrangement plan, namely the water zone, agricultural zone, and service zone. Where from each zoning there are functions of cultivation, research and education, and recreation. Not only that, the Cisoka Blue Lake Tourism Area was also analyzed based on its natural conditions, like based on topographical analysis and hydrological analysis. Where the analysis aims to obtain the functions and concepts that will be planned in accordance with the natural conditions in the Cisoka Blue Lake Tourism Area.Keywords : setup plan/ physical plan; the function of cultivation; the function of recreation; topography and hidrology AbstrakKawasan Wisata Telaga Biru Cisoka merupakan lahan pasca galian pasir yang menjadi tujuan destinasi wisata, yang memiliki 3 (tiga) danau dengan warna berbeda dan 1 (satu) danau sebagai Retention Basin. Kawasan Wisata Telaga Biru Cisoka memiliki potensi wisata yang berbasis agrowisata dan olahraga. Adanya tempat wisata seperti Telaga Biru Cisoka dapat menjadikan suatu daya tarik untuk memenuhi kebutuhan penduduk lokal dan menambahkan pendapatan ekonomi daerah. Maksud dan tujuan pada penelian di wisata ini yakni mengusulkan rencana penataan pada Kawasan Wisata Telaga Biru Cisoka dan mendapatkan hasil berupa masterplan Kawasan Wisata Telaga Biru Cisoka. Hal tersebut guna mengoptimalkan potensi Kawasan Wisata Telaga Biru Cisoka dan mewujudkan sebagai kawasan agrowisata dan olahraga. Kemudian menjadi masukan atau rekomendasi kepada para stakeholder yang berperan dalam perencanaan. Berdasarkan hasil analisis, Kawasan Wisata Telaga Biru Cisoka memiliki 3 (tiga) zonasi dalam rencana penataannya yakni zona air, zona pertanian, dan zona pendukung. Dimana dari masing-masing zonasi terdapat fungsi budidaya, penelitian dan edukasi, serta rekreasi. Tak hanya itu, Kawasan Wisata Telaga Biru Cisoka juga dianalisis berdasarkan kondisi alamnya, yakni berdasarkan analisis topografi dan analisis hidrologi. Dimana analisis tersebut bertujuan untuk mendapatkan fungsi dan konsep yang akan direncanakan yang sesuai dengan kondisi alam pada Kawasan Wisata Telaga Biru Cisoka.